A Proposal to Enhance Preservice Teacher’s Noticing (2018)
ABSTARCT: This paper presents a proposal for the development of ‘Teacher noticing’ with the help of dimensions taken from the teacher’s didactic-mathematical knowledge model, that makes up a Guide for Didactical Reflection. The proposal is based on a study conducted during a time span of two years while the preservice teachers were in their teaching practicum. The methodology was qualitative and data were taken in video, audio, observing rubrics, and interviews formats. The results not only indicate that the Guide can help develop teachers’ noticing, in order to identify and to question several specific domains of teacher knowledge involved in mathematics teaching, but also suggest that prospective teachers are moved into action and translate their noticing in didactic action during class. We hypothesize that preservice effective noticing occurs at the intersection of practice and discussion over the practice, with the help of ‘noticing tools’ with respect to the mathematical activities of students.